Papers - Observing Formation of Martensite in Certain Alloy Steels at Low Temperatures (With Discussion) - O. A. Knight; Helmut Muller-Stock (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1934)
The suppression of the austenite-martensite transformation that can be brought about by the addition of certain alloying elements, such as manganese or nickel, to plain carbon steel has been known for a long time, especially since Guillet's investigation at the beginning of this century. The extent to which the critical range is lowered depends upon the percentage and nature of the special element added. First the Arl point is lowered gradually, then at a certain percentage a sudden lowering to about 300" C. occurs. The addition of still larger percentages of the alloy may result in lowering the Ar, point to room temperature or below, in which case the steel remains austenitic at room temperature, especially after rapid cooling. The effect of alloying elements of this general type on the lowering of the transformation temperature is well illustrated by Sauveur(lJ$ in his Fig. 281a, reproduced here as Fig. 1. This type of curve is characteristic of both manganese and nickel though it requires about 21/2 times as much nickel as of manganese to produce the same result. The influence of nickel in retarding the transformation of austenite into the lower transition constituents is due to its lowering of the critical range of the steel, which is also well illustrated by Sauveur'l) (after Osmond) in his Fig. 284, reproduced here as Fig. 2. Scott('" presents a diagram illustrating the effect of manganese on the Ac3 and Ara points which is strikingly similar to the diagram above referred to in Fig. 2 concerning the effect of nickel. Lowering the critical range has the effect of increasing the viscosity, or, rigidity, of the alloy at the time when it is undergoing its transformation, which greatly slows down the transformation reaction velocity, and this, in turn, makes it easier to suppress, wholly or in part, the transformational changes. Reaction rates are normally much slower at low